THE AFFECT OF DOSAGE OF PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) BAMBOO ROOTS AT VARIOUS WATER LEVEL ON GROWTH AND YIELD OF Clitoria ternatea - S. M., Buwono; Trisnadewi, A. A. A. S.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aimed to determine the interaction between the dose of plant growth promoting rhizobacteria (PGPR) bamboo roots with different water level and the affected of each factor on the growth and yield of Clitoria ternatea plants. This research was conducted in the Greenhouse of Sading Village. This research lasted for 10 weeks, using a completely randomized design (CRD) factorial pattern. The first factor was PGPR dosage: 0 ml/pot (D0), 10 ml/pot (D1), 20 ml/pot (D2). The second factor consisted of soil moisture content, namely: 25% field capacity (K1), 50% field capacity (K2), 100% field capacity (K3). There were 9 treatment combinations and each treatment had 4 replications, so there were 36 experimental units. The variables observed were growth, yield, and growth characteristics variables. The results showed no interaction between PGPR dosage and different soil moisture content on all variables. The 20 ml/pot dose increased leaf area variables and the ratio of total forage dry matter to root dry matter. PGPR dosage of 20 ml/pot (D2) gave the highest mean on all variables except root dry weight and ratio of leaf dry weight to stem dry weight. Soil moisture content of 100% field capacity (K3) gave the highest average in all variables except root dry weight and ratio of leaf dry weight to stem dry weight. From this study it can be concluded that there is no interaction between PGPR dose of bamboo root with different soil moisture content on growth variables, yield, and growing characteristics. PGPR dose treatment of 20 ml/pot and soil moisture content treatment of 100% field capacity gave the best growth and yield in Clitoria ternatea plants.